Pengaruh Corporate Social Respon (CSR) dan Return on Assets (ROA) Terhadap Nilai Perusahaan - Sinta Fitriani; Eva Maria Sulastri; Kamaluddin Rahmat (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) and Return on Assets (ROA) on firm value in the coal mining sector listed on the Indonesia Stock Exchange during the period 2021–2024. The study uses a quantitative approach with a causal associative method and secondary data obtained from annual reports and sustainability reports of coal companies. The sample was selected using purposive sampling, resulting in 11 companies and 44 observations. Data analysis was performed using multiple linear regression after passing classical assumption tests. The results show that CSR has a positive effect on firm value but is not statistically significant. ROA has a negative effect, also not significant. The coefficient of determination (R Square) of 0.107 indicates that CSR and ROA can only explain 10.7% of the variation in firm value, while the remaining variation is influenced by other factors not examined in this model. This study strengthens the relevance of stakeholder theory, legitimacy theory, and signaling theory in explaining firm value in the high-risk extractive industry sector. The novelty of this research lies in its focus on the coal sector and the use of a more recent period. The study recommends that coal companies strategically integrate CSR and improve financial performance transparency to support the creation of long-term firm value.